Fuzzy OPF incorporating UPFC - Venkatesh, B.; George, M.K.; Gooi, H.B. (2004)
A new optimal reactive power flow (ORPF) method is proposed which considers the inclusion of unified power flow controllers (UPFC). The modelling and inclusion of UPFC in the solution of power flow equations is presented. The ORPF problem is formulated as a fuzzy optimisation problem considering the objectives of minimising system transmission loss and obtaining the best voltage profile. The fuzzy formulation of the ORPF problem is solved using an EP algorithm. The proposed method is applied on the 6-bus and 57-bus IEEE test systems and on a 191-bus Indian electric power system. The results demonstrate the applicability of the method.